Estrutura e germinação de sementes de pequizeiro antes e após a dispersão - Iara Veloso Rodrigues (2017)
Caryocar brasiliense Camb. (Caryocaraceae), pequizeiro, is a tree species with wide distribution in the Cerrado. Its fruits are widely collected for human consumption, the pharmaceutical industry and cosmetics. The present work aimed to characterize biometric, anatomical and physiological aspects of the development of fruits and seeds of C. brasiliense, as well as to evaluate the effect of dormancy overcoming treatments on the physiological quality of its seeds. In the first work, during the development of the fruit biometric evaluations were carried out in the pericarp and in the seed and anatomical, histochemical, ultrastructural evaluations and in vitro and ex vitro culture of the embryos. In the second, germinability, seedling emergence, IVE and seed mortality in freshly dispersed (control), treated with GA3 (375 mg/L), stored for 30 days and for 120 days. In addition, malondialdehyde (MDA) was quantified from freshly dispersed seeds and stored for 30, 120 and 480 days. The development of the fruit occurred in about 90 days and was characterized by three phases: i) histodifferentiation; ii) maturation of the endocarp; iii) mesocarp and seed maturation. The acaracled endocarp reached maturity early, acting as the protective structure of the embryo. The mesocarp and the seed presented increased dry matter content along the development of the fruit. Embryos showed a high degree of differentiation (early leaf and vascular bundles) and early germination capacity at 40 days after anthesis (DAA). The beginning of the deposition of embryonic reserves coincided with the acquisition of tolerance to dehydration, reached near the 50 days DAA. The pronounced seminal dormancy was related to the tissues adjacent to the embryo. The storage and treatment with GA3 were efficient in breaking dormancy and promoting germination, but increased the deterioration of seeds. The newly dispersed seeds (control) initially presented a lower germination and emergence, followed by a stabilization (between May and August), resuming the emergence with increasing ambient temperature. A longer time of storage of the pyrenes (120 days) generated high rates of seed deterioration and low emergence; probably due to the increase in the production of reactive oxygen species, verified by the increase of MDA.